Vascular Remodeling in Experimental Hypertension - Norma R. Risler; Montserrat C. Cruzado; Roberto M. Miatello (The Scientific World Journal)
The basic hemodynamic abnormality in hypertension is an increased peripheral resistance that is due mainly to a decreased vascular lumen derived from structural changes in the small arteries wall, named (as a whole) vascular remodeling. The vascular wall is an active, flexible, and integrated organ made up of cellular (endothelial cells, smooth muscle cells, adventitia cells, and fibroblasts) and noncellular (extracellular matrix) components, which in a dynamic way change shape or number, or reorganize in response to physiological and pathological stimuli, maintaining the integrity of the vessel wall in physiological conditions or participating in the vascular changes in cardiovascular diseases such as hypertension. Research focused on new signaling pathways and molecules that can participate in the mechanisms of vascular remodeling has provided evidence showing that vascular structure is not only affected by blood pressure, but also by mechanisms that are independent of the increased pressure. This review will provide an overview of the evidence, explaining some of the pathophysiologic mechanisms participating in the development of the vascular remodeling, in experimental models of hypertension, with special reference to the findings in spontaneously hypertensive rats as a model of essential hypertension, and in fructose-fed rats as a model of secondary hypertension, in the context of the metabolic syndrome. The understanding of the mechanisms producing the vascular alterations will allow the development of novel pharmacological tools for vascular protection in hypertensive disease.